Study on quality in 3D digitisation of tangible cultural heritage: mapping parameters, formats, standards, benchmarks, methodologies, and guidelines : final study report - Ioannides, Marinos (My University, 2022)
This study was commissioned by the Commission to help advance 3D digitisation across Europe and thereby to support the objectives of the Recommendation on a common European data space for cultural heritage (C(2021) 7953 final), adopted on 10 November 2021. The Recommendation encourages Member States to set up digital strategies for cultural heritage, which sets clear digitisation and digital preservation goals aiming at higher quality through the use of advanced technologies, notably 3D. The aim of the study is to map the parameters, formats, standards, benchmarks, methodologies and guidelines relating to 3D digitisation of tangible cultural heritage. The overall objective is to further the quality of 3D digitisation projects by enabling cultural heritage professionals, institutions, content-developers, stakeholders and academics to define and produce high-quality digitisation standards for tangible cultural heritage. This unique study identifies key parameters of the digitisation process, estimates the relative complexity and how it is linked to technology, its impact on quality and its various factors. It also identifies standards and formats used for 3D digitisation, including data types, data formats and metadata schemas for 3D structures. Finally, the study forecasts the potential impacts of future technological advances on 3D digitisation.
Keywords: Culture; Information technology and telecommunications